Information generating function for order statistics and mixed reliability systems. Issue 22 (21st September 2021) - Kharazmi, Omid; Balakrishnan, Narayanaswamy
Abstract: In this work, we consider the information generating measure and relative information generating measure and develop some associated results concerning mixed systems with independent and identically distributed components. We then provide some comparison results for mixed systems using these measures.